A Systematic Review and Meta-Analysis of the Association between Uric Acid and Allantoin and Rheumatoid Arthritis - Angelo Zinellu; Arduino A. Mangoni (MDPI AG, 2023)
Alterations in the circulating concentrations of uric acid and its degradation product, allantoin, might account for the systemic pro-oxidant state and the increased cardiovascular risk in rheumatoid arthritis (RA). We sought to address this issue by conducting a systematic review and meta-analysis of the association between the plasma/serum concentrations of uric acid and allantoin and RA. We searched PubMed, Scopus, and Web of Science from inception to 20 June 2023 for studies comparing plasma/serum concentrations of uric acid and allantoin between RA patients and healthy controls. We assessed the risk of bias with the JBI Critical Appraisal Checklist for analytical studies and the certainty of evidence with the Grades of Recommendation, Assessment, Development and Evaluation (GRADE) Working Group system. In the 19 studies selected for analysis, there were non-significant differences in uric acid concentrations between RA patients and controls (standard mean difference, SMD = 0.11, 95% CI −0.07 to 0.30, p = 0.22; I2 = 87.9%, p < 0.001; low certainty of evidence). By contrast, the concentrations of allantoin were significantly higher in RA patients (SMD = 1.10, 95% CI 0.66 to 1.55, p < 0.001; I2 = 55.6%, p = 0.08; extremely low certainty of evidence). In meta-regression, a significant association was observed between the SMD of uric acid concentrations and body mass index, a risk factor for atherosclerosis and cardiovascular disease (t = 3.35, p = 0.007). Our study has shown a significant increase in the concentrations of the oxidative stress biomarker allantoin in patients with RA. Further research is warranted to investigate the interplay between uric acid, allantoin, redox balance, and cardiovascular disease in this group. (PROSPERO registration number: CRD42023441127).